2016
DOI: 10.1038/srep37055
|View full text |Cite
|
Sign up to set email alerts
|

Near-Earth object hazardous impact: A Multi-Criteria Decision Making approach

Abstract: The impact of a near-Earth object (NEO) may release large amounts of energy and cause serious damage. Several NEO hazard studies conducted over the past few years provide forecasts, impact probabilities and assessment ratings, such as the Torino and Palermo scales. These high-risk NEO assessments involve several criteria, including impact energy, mass, and absolute magnitude. The main objective of this paper is to provide the first Multi-Criteria Decision Making (MCDM) approach to classify hazardous NEOs. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…The screening of the superior cultivars and the selection of the appropriate parents to perform crossbreeding are two main approaches to enlarge the planting area of the target plant, and both approaches should be based on the resource evaluation 4,6 . In this study, we adopted the AHP to evaluate the peony performances, which had been confirmed as a classic and highly effective MCDM methodology to evaluate the specific goals 14,32,33 . This method has been widely used in many scientific fields, such as astronomy, geography, energy science, environmental ecology, healthcare, management and engineering 13,34,4348 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The screening of the superior cultivars and the selection of the appropriate parents to perform crossbreeding are two main approaches to enlarge the planting area of the target plant, and both approaches should be based on the resource evaluation 4,6 . In this study, we adopted the AHP to evaluate the peony performances, which had been confirmed as a classic and highly effective MCDM methodology to evaluate the specific goals 14,32,33 . This method has been widely used in many scientific fields, such as astronomy, geography, energy science, environmental ecology, healthcare, management and engineering 13,34,4348 .…”
Section: Discussionmentioning
confidence: 99%
“…The construction of a completed MCDM evaluation system includes some common steps, such as choosing indices, making criteria and assigning weights 13,14,32 (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, software related to assessment methods will be designed and applied in the assessment process. (3) For the uncertainty of experts' evaluations, uncertainty theory will be studied in the future [35,36,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…After explaining the purpose of the study, briefly, they were requested to fill in the questionnaire. SPSS version 16.0 was used to analyze gathered data from completed questionnaires. Normality of the data was tested using the Kolmogorov-Smirnov test.…”
Section: Methodsmentioning
confidence: 99%
“…13 It is a multi-criteria decision making model used to compare a set of choices by determining weights for each measure. [14][15][16][17] Lost of studies have been presented in the area of marketing using Topsis technique. Mehralian et al 18 have identified and prioritized the critical success factors within pharmaceutical industries by Topsis technique.…”
Section: Introductionmentioning
confidence: 99%